Diluted Bothrops Atrox Time (Dbat). A New Assay to Detect Lupus Anticoagulant - Oviedo Donayre, Pilar (2000)
OBJECTIVE: To validate a new assay for lupus anticoagulant (LA) that employs crude diluted venom of Bothrops atrox (dBat) comparing it with four phospholipid - dependent assays. MATERIAL AND METHODS: Citrated serum samples from 70 inpatients clinically diagnosed as having SLE, primary antiphospholipid syndrome (PAPS), thrombosis/embolism or suspected thrombosis from the Hospital Guillermo Almenara Irigoyen over 12 months, were assayed. dRVVT was used as comparative test for reference values. RESULTS: 30 samples were positive to dBat and dRVVT tests plus at least another one of the remain assays; 27 samples had negative results in all assays and there were 13 in which dBat results had not concordance with dRVVT results (p>0,05). 47,8% of SLE, 71,4% of PAPS, 75% of thrombosis and 47,8% of suspected thrombosis cases were LA (+). CONCLUSIONS: The high concordance between dBat and dRVVT results, higher that those found with another tests, as well as their close relationship with clinical features, permit us to conclude that dBat assay can be used to detect LA.